Quality Assurance for Patients with Breast Cancer – the Impact of Clinical Cancer Registries - Inwald, E. C.; Klinkhammer-Schalke, M.; Koller, M.; Ortmann, O. (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: Since 2000 all service providers in the German healthcare system are legally obliged to take part in quality assurance (QA) procedures as stipulated in Book Five of the German Social Code. Clinical cancer registries provide methodological tools to assess the quality of structures, processes and outcomes. The aim of this study was to analyze the consequences of guideline-concordant treatment using two examples of quality indicators: endocrine therapy (adjuvant hormonal therapy, AHT) to treat patients with steroid hormone receptor (SHR)-positive breast cancer and trastuzumab therapy to treat patients with HER2-positive breast cancer. Material and Methods: Data from the Tumor Center Regensburg (Bavaria, Germany) included all female patients listed in the registry with primary, non-metastatic invasive breast cancer diagnosed between 2000 and 2012. Results: A total of 6164 patients with invasive breast cancer and known HER2 status were analyzed. 1134 patients (18.4 %) had HER2-positive and 5346 patients (86.7 %) had SHR-positive breast cancer. Premenopausal patients with HER2-positive breast cancer receiving trastuzumab had a 7-year OS rate of 93.8 % compared to 86.8 % of patients who did not receive trastuzumab (p = 0.079). Similarly, postmenopausal patients with HER2-positive breast cancer treated with trastuzumab had better 7-year OS rates (87.3 %) than patients who did not receive the antibody (76.7 %) (p < 0.001). Premenopausal patients with SHR-positive breast cancer receiving AHT had a 7-year OS rate of 95.2 % compared to 75.9 % of patients who did not receive AHT (p < 0.001). Equally, postmenopausal patients treated with AHT had a 7-year OS rate of 83.8 % compared to 64.1 % without AHT (p < 0.001). Conclusion: Clinical cancer registries depend on the cooperation of the various health service providers to generate data that are essential for QA for breast cancer patients.
Keywords: breast cancer; cancer registry; quality assurance